2022
DOI: 10.1111/jpm.12834
|View full text |Cite
|
Sign up to set email alerts
|

“They have more than enough to do than patch up people like me.” Experiences of seeking support for self‐harm in lockdown during the COVID‐19 pandemic

Abstract: Accessible Summary What is known on the subject? In the initial months of the pandemic, there was no significant increase in demand for mental health services During the pandemic, there was an increase in people reporting an increase in suicidal thoughts. Understanding of the experience of seeking help for self‐harm during lockdown is lacking, in terms of availability and accessibility of support services What the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Given the impact of the pandemic on youth mental health, it is not surprising that levels of self-harm appear somewhat elevated when compared to pre-pandemic levels. While young people of the present sample may have engaged in self-harm before the COVID-19 outbreak, detected levels in this study may appear elevated because mental health services were significantly interrupted by prolonged lockdowns, which have been a barrier for seeking help (Sass et al, 2022). Thus, young people who could not access their standard level of care and support may engaged more frequently in self-harm.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Given the impact of the pandemic on youth mental health, it is not surprising that levels of self-harm appear somewhat elevated when compared to pre-pandemic levels. While young people of the present sample may have engaged in self-harm before the COVID-19 outbreak, detected levels in this study may appear elevated because mental health services were significantly interrupted by prolonged lockdowns, which have been a barrier for seeking help (Sass et al, 2022). Thus, young people who could not access their standard level of care and support may engaged more frequently in self-harm.…”
Section: Discussionmentioning
confidence: 67%
“…However, the true rates of self-harm maybe even higher. This realisation becomes increasingly important especially considering that during the first months of the pandemic the strict lockdown measures have disrupted mental health services and supports, which in turn imposed barriers for those who self-harm to access help (Sass et al, 2022). These lockdown measures may have masked the true mental health burden in young people during the pandemic (Kaess, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These studies nonetheless provide valuable evidence relevant to the findings of this review. It was found that individuals presented to the emergency department less frequently during the pandemic for suicide ideation (Sass et al, 2022;Sveticic et al, 2021). Participants described feeling like a burden to others due to an awareness of all healthcare services struggling under the pressure of COVID-19 (Sass et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that individuals presented to the emergency department less frequently during the pandemic for suicide ideation (Sass et al, 2022;Sveticic et al, 2021). Participants described feeling like a burden to others due to an awareness of all healthcare services struggling under the pressure of COVID-19 (Sass et al, 2022). Digital tools can serve as a valuable tool to address the helpseeking needs of individuals, particularly those who are hesitant to visit hospitals, especially amidst pandemic situations and where there are concerns about being judged.…”
Section: Discussionmentioning
confidence: 99%